The Left-wing Populist Revolt in Europe: SYRIZA in Power - Markou, Grigoris (Identities: Journal for Politics, Gender and Culture, 2017)
Author(s): Grigoris Markou Title (English): The Left-wing Populist Revolt in Europe: SYRIZA in Power Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 14, No. 1 (Winter 2017) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 148-154 Page Count: 7 Citation (English): Grigoris Markou, “The Left-wing Populist Revolt in Europe: SYRIZA in Power,” Identities: Journal for Politics, Gender and Culture, Vol. 14, No. 1 (Winter 2017): 148-154.